Implementation of SITENSI Digital Application to Improve Hypertension Patient Compliance in Health Management: Penerapan Aplikasi Digital SITENSI untuk Meningkatkan Kepatuhan Pasien Hipertensi dalam Pengelolaan Kesehatan - ardiani, Dewi Ulfah Ardiani; Tikfi Andriani; Supiah Farida; Aluh Eka Novianty; Nurfika Asmaningrum; Ardiana, Anisah; Baiq Trisna Satriana; Ida Ayu Manik Fitriani Utami (KHD Production, 2025)
Hypertension is one of the most prevalent chronic diseases in the working area of Karang Taliwang Public Health Center, Mataram City. The main challenges in hypertension management include patients’ low adherence to control schedules and limited health literacy. This community service activity aims to improve patient adherence and understanding through the implementation of a digital application called “SITENSI” (Blood Pressure and Hypertension Education Information System). The activity was conducted from June to July 2025 through initial observation, dissemination, digital education, cadre training, and application trials in local health posts and the primary health center. A total of 20 hypertensive patients participated in the pre- and post-tests. The results indicated a significant increase in knowledge scores from 4.8 (pre-test) to 15.4 (post-test), showing a 10.6-point improvement. Additionally, cadres and health workers responded positively to the application’s user-friendliness and educational features. The implementation of SITENSI proves effective in supporting technology-based primary health care transformation and strengthening the role of nurses and community health workers in hypertension management.